2009
DOI: 10.1038/nchembio.168
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of a GPR30 antagonist

Abstract: Estrogen is central to many physiological processes throughout the human body. We have previously shown that the G protein-coupled receptor GPR30/GPER, in addition to classical nuclear estrogen receptors (ERα/β), activates cellular signaling pathways in response to estrogen. In order to distinguish between the actions of classical estrogen receptors and GPR30, we have previously characterized a selective agonist of GPR30, G-1 (1). To complement the pharmacological properties of G-1, we sought to identify an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
451
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(476 citation statements)
references
References 44 publications
(53 reference statements)
24
451
0
1
Order By: Relevance
“…EdU incorporation was assessed by the Click-iT EdU flow cytometry assay kit (Lifetech, Carlsbad, CA). To assess the impact of the GPER antagonist, G15 47 (Calbiochem-Novabiochem), on E2 or G1 effects on proliferation, cells were treated with G15 (µmol/L) for 15 minutes before addition of these agonists.…”
Section: Assessment Of Regulation Of Dna Synthesis As An Index Of Promentioning
confidence: 99%
“…EdU incorporation was assessed by the Click-iT EdU flow cytometry assay kit (Lifetech, Carlsbad, CA). To assess the impact of the GPER antagonist, G15 47 (Calbiochem-Novabiochem), on E2 or G1 effects on proliferation, cells were treated with G15 (µmol/L) for 15 minutes before addition of these agonists.…”
Section: Assessment Of Regulation Of Dna Synthesis As An Index Of Promentioning
confidence: 99%
“…Однако в данном случае процесс деградации не запускается, транс-портеры остаются в резерве около мембраны [31]. Дополнительной иллюстрацией влияния эстрадиола на серотонинергическую систему является его антиде-прессивная активность [32] и то, что G15 (антагонист GPER1) отменяет антидепрессивный эффект E 2 (и G1) в экспериментальной модели.…”
Section: эффекты эстрогенов в цнсunclassified
“…It suggested that G-1 inhibitory effect in SKOV-3 and OVCAR-3 ovarian cancer cells due to specific activation of GPER-1 and not to cytotoxic properties. To explore the involvement of GPER-1 activation in G-1-induced cell growth inhibition we extended our experiments using G-15 a recently discovered GPER-1 receptor antagonist [21]. Pre-incubation of SKOV-3 and OVCAR-3 cells with 1 μM G-15 was able to block the inhibitory effect of G-1 ( Figure 4).…”
Section: Effect Of Gper-1 Stimulation On Ovarian Cancer Cell Prolifermentioning
confidence: 99%